Good practice guidelines for clinical psychologists working in paediatric cochlear implant teams. (November 2013) - Bathgate, Fionna; Bennett, Emily; Cropper, Jenny; Edwards, Lindsey; Emond, Alice; Gamble, Caroline; Kentish, Rosie; Samuel, Victoria
Abstract : There are relatively few clinical psychologists working in paediatric cochlear implant centres in the UK and in this respect we lag behind other countries such as the USA and The Netherlands. In an effort to promote the added value our profession can offer teams, the clinical psychologists working in paediatric CI centres have put together good practice guidelines. This article outlines the rationale for putting together the guidelines, highlights the unique contribution clinical psychologists can offer, outlines the evidence base for psychological input in this clinical population, and offers a fictional case study for illustration.